The Posthuman Condition in 21st Century Literature and Culture
X, 282 p.
Keywords: More than a decade after its first definitions, critical posthumanism has become consolidated as a key discourse for the understanding of our contemporary state of being within what has been called the paradigm of posthumanity, but also, crucially, as an ideology and a praxis that guides our engagements with the world around us. This double dimension characterizes the contributions to this volume. They resort to critical posthumanism in its most recent developments as a set of tools for critical and cultural analysis of our posthuman times, as posthuman(ist) concerns manifest in our cultural products. This volume studies the most recent evolutions in the field of critical posthumanism as represented in key novels and other (screened) popular cultural products produced in the first and second decades of the twenty-first century. Resorting to the analytical tools provided by critical posthumanist theory in cross-disciplinary dialogue with other fields—such as transhumanism, feminist, gender and queer theory, vulnerability studies, new materialism, critical animal studies and environmental theory—the scholars whose work this volume showcases bear witness to how literature and popular culture have been influenced and impressed by posthumanism. María Ferrández-Sanmiguel, Associate Professor at the University of Zaragoza, Spain, specializes in North American Literature, focusing on contemporary US fiction and ethics. Her research explores the posthuman and nonhuman elements in speculative fiction. Recent works include articles in Critique and Extrapolation, and the monograph Trauma, Gender and Ethics in the Works of E.L. Doctorow (2020). Esther Muñoz-González, Associate Professor at the University of Zaragoza, Spain, specializes in contemporary US fiction with a posthumanist focus. Her research explores dystopian representations of the future and cli-fiction in Gothic texts. She has published in impactful journals and edited volumes, including a recent monograph titled Posthumanity in the Anthropocene: Margaret Atwood Dystopias (2023). Carmen Laguarta-Bueno, a University of Zaragoza faculty member, specializes in contemporary US fiction, exploring trauma, transhumanism, critical posthumanism, and bioethics. Author of Representing (Post)Human Enhancement Technologies in Twenty-First Century US Fiction (2022), her recent essays delve into virtual immortality, transhumanism, metafiction, and the ethical aspects of enhancing human happiness through biotechnology. Chapters 1, 5, 7,8 and 12 are available open access under a Creative Commons Attribution 4.0 International License via Springerlink.